DNA damage responsive miR-33b-3p promoted lung cancer cells survival and cisplatin resistance by targeting p21WAF1/CIP1. Issue 21 (1st November 2016) - Xu, Shun; Huang, Haijiao; Chen, Yu-ning; Deng, Yun-ting; Zhang, Bing; Xiong, Xing-dong; Yuan, Yuan; Zhu, Yanmei; Huang, Haiyong; Xie, Luoyijun; Liu, Xinguang
ABSTRACT: Cisplatin is the most potent and widespread used chemotherapy drug for lung cancer treatment. However, the development of resistance to cisplatin is a major obstacle in clinical therapy. The principal mechanism of cisplatin is the induction of DNA damage, thus the capability of DNA damage response (DDR) is a key factor that influences the cisplatin sensitivity of cancer cells. Recent advances have demonstrated that miRNAs (microRNAs) exerted critical roles in DNA damage response; nonetheless, the association between DNA damage responsive miRNAs and cisplatin resistance and its underlying molecular mechanism still require further investigation. The present study has attempted to identify differentially expressed miRNAs in cisplatin induced DNA damage response in lung cancer cells, and probe into the effects of the misexpressed miRNAs on cisplatin sensitivity. Deep sequencing showed that miR-33b-3p was dramatically down-regulated in cisplatin-induced DNA damage response in A549 cells; and ectopic expression of miR-33b-3p endowed the lung cancer cells with enhanced survival and decreased γH2A.X expression level under cisplatin treatment. Consistently, silencing of miR-33b-3p in the cisplatin-resistant A549/DDP cells evidently sensitized the cells to cisplatin. Furthermore, we identified CDKN1A (p21) as a functional target of miR-33b-3p, a critical regulator of G1/S checkpoint, which potentially mediated the protection effects of miR-33b-3p against cisplatin. In aggregate, our results suggested that miR-33b-3p modulated the cisplatin sensitivity of cancer cells might probably through impairing the DNA damage response. And the knowledge of the drug resistance conferred by miR-33b-3p has great clinical implications for improving the efficacy of chemotherapies for treating lung cancers.